Sosialisasi & Inventarisasi Potensi Desa Wisata di Desa Cikalong Kecamatan Cimaung Kabupaten Bandung - Reza Martani Surdia; Apriadi Budi Raharja; Budi Heri Pirngadie; Supratignyo Aji (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2019)
Palasari Village, Cikalong Village has the potential of the agricultural and plantation sectors, this is illustrated by the population structure of the Cikalong Village based on the type of livelihood of the people who also use the land distributed. It is unfortunate that the potential of agriculture isn’t seen from other perspectives as a tourist attraction. "Non-mass tourism" or known as an alternative type of tourism that is more directed at small groups organized to look for things related to the first that are related to culture, environment, or specific place. Therefore, a tourist village that presents the potential for rural nuances that have distinctive characteristics becomes a tourist destination. Tourism village is a rural area that has several unique characteristics that are prepared for tourist destinations. Based on the results of an inventory of tourism potential, the partner village of PpM (pengabdian kepada masyarakat) has tourism potential related to folklore related to "Batu Cinta", and a panorama of agriculture against the backdrop of Mount Puntang hills. However, there are challenges that discuss the partnership in developing the attraction object, planting permit, tourism awareness, and awareness of environmental cleanliness.